A real-world experience of venetoclax combined with hypomethylating agents vs. monotherapy hypomethylating agents in patients with myelodysplastic syndromes and chronic myelomonocytic leukemia patients - Zhang, Ludan; Ge, Rui; Pan, Deng; Yue, Pengjie; Zhang, Jingwen; Bian, Renjie; Yan, Xiaojing (Frontiers in Pharmacology, 2024)
Introduction: Current clinical research has reported the effectiveness and safety of venetoclax in combination with hypomethylating agents (VEN-HMA) in patients with myelodysplastic syndromes (MDS) and chronic myelomonocytic leukemia (CMML). Thus, this study aimed to examine the effectiveness and safety of VEN-HMA therapy in patients with MDS and CMML and compared its short-term and long-term therapeutic effects with HMA monotherapy. Method: We analyzed data from our center, comprising 19 patients with MDS and CMML who received VEN-HMA therapy, compared to 32 patients treated with HMA monotherapy. Results: The overall response rate (ORR) in the VEN-HMA group was 73.7%, compared to 59.4% in the HMA group. The survival analysis revealed that the median overall survival (mOS) time in the VEN-HMA group was 16 months, with a median progression-free survival (mPFS) time of 9 months, both of which were longer than those observed in the HMA group (p < 0.05). Key adverse events (AEs) included grade 3–4 neutropenia (89.5% in VEN-HMA group vs. 87.5% in HMA group), grade 3–4 thrombocytopenia (73.7% vs. 71.9%), and anemia (73.7% vs. 90.6%). Infection of grade 3 or higher occurred in 63.2% of patients in the VEN-HMA group and 65.6% of patients in the HMA group. Discussion: Our study has confirmed the effectiveness and safety of the combined treatment of HMAs and venetoclax, which offers significant advantages to patients due to the relatively high and rapid response rates.